The Role of Matrix Metalloproteinases a nd Tissue Inhibitors of Metalloproteinases in the Progression of Astrocytomas - Motta, Fábio; Canalle, Renata; Yoshioka, France; Pinto, Giovanny; Harada, Lúcia; Jurnior, Carlotti; Valera, Elvis; Scrideli, Carlos; Tone, Luiz (IntechOpen, 2011)
None